Microcystin-LR promotes epithelial-mesenchymal transition in colorectal cancer cells through PI3-K/AKT and SMAD2. (4th January 2017) - Ren, Yan; Yang, Mengli; Chen, Meng; Zhu, Qiangqiang; Zhou, Lihua; Qin, Wei; Wang, Ting
Graphical abstract: Highlights: Microcystin-LR promotes EMT and its associated tumor cell invasion and migration in colorectal cancer cells. Microcystin-LR enhances the expression of SMAD2. Microcystin-LR induces EMT in colorectal cancer cells through PI3-K/AKT signal pathway. Links the PI-3K/AKT signal pathway to SMAD2 signaling in microcystin-LR induced EMT in colorectal cancer cells. The manuscript broadens the understanding of the mechanisms that MC-LR accelerated cancer progress. Abstract: Increasing evidences suggest that microcystins, a kind of toxic metabolites, produced by cyanobacteria in contaminated water may contribute to the aggravation of the human colorectal carcinoma. Our previous study showed that microcystin-LR (MC-LR) exposure caused significant invasion and migration of colorectal cancer cells. However, the roles of MC-LR in regulating epithelial-mesenchymal transition (EMT) in colorectal cancer cells remain unknown. In our study, we observed that MC-LR treatment decreased epithelial marker E-cadherin expression and up-regulated the levels of mesenchymal markers Vimentin and Snail in colorectal cancer cells. Moreover, MC-LR stimulated protein expression of SMAD2 and phospho-SMAD2 by PI3-K/AKT activation. The activated PI3-K/AKT and SMAD2 signaling largely accounted for MC-LR-induced EMT, which could be reversed by SMAD2 RNA interference or PI3-K/AKT chemical inhibitor in colorectal cancer cells. Our results show that MC-LR could induce SMAD2 expression to promote colorectal cancer cells EMT, which not only provides a mechanistic insight on MC-LR promotes EMT in colorectal cancer cells, but also support to the development of therapies aimed at SMAD2 in colorectal cancer induced by MC-LR.